A strategy to evaluate programme level outcomes - Shuaib N.H.; Anuar A.; Salleh H.; Hasan M.H. (2023)
Evaluation of the attainment or achievement of Programme Outcomes (PO) is one of the essential parts in Outcome-Based Education (OBE) system. Direct and indirect assessment methods may be used in evaluating the achievement of PO. Direct assessment method normally uses data from final exams, test, quizzes, assignments or projects for the evaluation. Other methods that are used include course survey, peer review, lecturers' observation and industry survey. This paper discusses the strategy that the Mechanical Engineering Department employed to evaluate the PO for its Bachelor of Mechanical Engineering Programme. Initially the department only use direct measurement method to evaluate the programme outcomes. Upon receiving feedback from several constituencies, the department decided to revise and come up with a new strategy to evaluate the programme outcomes. In this strategy, only the courses that would contribute significantly to the PO are selected. Suitable measurement tools are identified and the attainment targets or the performance criteria are set. The relevant data is then collected, analysed and compared to the attainment target. If the target value is not attained, suggestions for improvement will be made and implemented. This method is expected to give a more reflective and accurate result while reducing the need to carry out too much data collection and analysis. 2009 IEEE.